2019
DOI: 10.22190/fuacr1901019k
|View full text |Cite
|
Sign up to set email alerts
|

Soft Robot Positioning Using Artificial Neural Network

Abstract: The experiment investigated the performance of an artificial neural network in solving the inverse kinematic problem of a soft robot. For this purpose, a simple soft robot was designed of building blocks, stringed on three rubber hoses, and an actuating system, to provide the hydraulic pressure. An axial extending of a hose, while the others are in the relaxed state, results in bending of the robot. The network was employed, as a black box, to approximate the behavior of the system. In accordance with the purp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…The number of hidden layers was decided considering the results presented in the work of Kovandžić [ 23 ], where it was shown that a multilayer network compared to a single hidden layer network did not present a significant improvement. For this reason, we decided to use six hidden layers in our network.…”
Section: Implementation Of the Pcc And The Neural Networkmentioning
confidence: 99%
“…The number of hidden layers was decided considering the results presented in the work of Kovandžić [ 23 ], where it was shown that a multilayer network compared to a single hidden layer network did not present a significant improvement. For this reason, we decided to use six hidden layers in our network.…”
Section: Implementation Of the Pcc And The Neural Networkmentioning
confidence: 99%